Diallyl disulfide inhibits growth and metastatic potential of human triple‐negative breast cancer cells through inactivation of the β‐catenin signaling pathway. Issue 6 (29th April 2015) - Huang, Jing; Yang, Bing; Xiang, Tingxiu; Peng, Weiyan; Qiu, Zhu; Wan, Jingyuan; Zhang, Li; Li, Hongyuan; Li, Hongzhong; Ren, Guosheng
<x xml:space="preserve">Abstract</x> Scope Although diallyl disulfide (DADS), an important garlic (Allium sativum) derivative, has exhibited potential anticancer activity, the molecular mechanism of this activity remains unknown. In this study, we evaluated the antitumor activity of DADS in triple‐negative breast cancer (TNBC) cell lines based in vitro and in vivo models. Methods and results We found that treatment with DADS resulted in decreased viability, increased apoptosis, and suppression of metastatic potential in TNBC cells. Furthermore, DADS induced dysregulation of B‐cell lymphoma (Bcl)‐2 family members, downregulation of matrix metalloproteinase (MMP)‐9 and reversal of the epithelial–mesenchymal transition (EMT). Interestingly, DADS significantly inhibited activation of the β‐catenin signaling pathway, which regulated Bcl‐2 family members, MMP‐9 and EMT in TNBC cells. Consistent with these in vitro findings, we also verified the anticancer potential of DADS in MDA‐MB‐231 xenograft mice. Treatment with DADS significantly reduced tumor volume and weight and increased apoptosis in these mice, while the expression of active β‐catenin was decreased, and the downstream molecules were dysregulated. Conclusion Our results show that the antitumor effect of DADS on TNBC cells is mediated by the β‐catenin pathway, suggesting that DADS could be used as a potential therapeutic agent for treating or preventing breast cancer.